Social Media Influence on Gen Ys’ Consumer Purchase Behaviour: A Developing Country’s Perspective - Jayanty KUPPUSAMY; Ajitha ANGUSAMY; Manesha RAJARATHNAM (Communications of International Proceedings, 2022)
The development of online social media networks has enabled it to expand from an initial function of a platform of communication and interaction among individuals to social commerce. Therefore, people are able to purchase items, provide feedbacks and obtain reviews through social media. The number of social media users and the usage is increasing including for the purpose of social commerce. Generation Y are those who are very digitally active. Thus, the study aims to examine social media’s influence on Gen Y’s consumer purchase behaviour. The factors considered in this study include perceived usefulness, perceived ease of use, word-of-mouth, and information quality. Questionnaire is used to collect the data. A sample of 200 respondents is selected through purposive sampling. It is found that perceived ease of use, word of mouth, and information quality in social media have significant impact on Gen Y’s consumer purchase behaviour. Therefore, businesses that uses social media as a medium of marketing need to focus on these factors to have a better business outcome.
Keywords: social media; consumer purchase behaviour; perceived ease of use; word of mouth